Pengembangan Motif Dekorasi Pada Benda Keramik Fungsional Di BTIKK BPPT Bali - I Wayan Agus Arya Santika Santika; Ni Made Rai Sunarini; I Made Mertanadi (Hastagina : Jurnal Kriya Seni, 2022)
Internship activity is a process for students to develop the knowledge they have or get in college and add knowledge to a job or project that is worked on by a company or craftsman. And still related to the field. The reason for choosing BTIKK BPPT Bali as an internship place is because this institution is engaged in ceramics and is still related to the education that the author took in lectures, namely in the field of ceramics, besides that the author wants to add new insights or new knowledge about the world of ceramics and also wants to develop skills which are owned. Another reason is that there are problems that the author faces related to ceramics, the problems include a lack of understanding about decorating techniques, types of decorations, and so on. The method of implementing the MBKM internship is carried out in the initial stages, namely surveys and preliminary research. Proceed to the next stage, namely starting to carry out internship activities. At this stage, the author began to learn related to the production process at BTIKK BPPT Bali, such as forming a ceramic body, decorating ceramics, and also glazing. The technique used in this data collection uses techniques including observation, interviews, and documentation. The writer hopes that with the Merdeka Learning Independent Campus (MBKM) internship, students can gain new knowledge related to the field in which they student is involved.